Gamified Learning Innovation: Enhancing Geometry Education and Student Engagement through Role-Playing Games - Herlansyah, Rhido; Retnawati, Heri (Universitas Islam Negeri Raden Intan Lampung, 2024)
This study aimed to develop a role-playing game-based learning medium for teaching flat-sided geometric shapes in mathematics, with the dual objectives of enhancing students’ interest and academic performance while meeting the criteria of validity, practicality, and effectiveness. Utilizing a research and development methodology, the study followed several stages: needs analysis, planning, game design and development, validation by media and subject matter experts, iterative revisions, media testing, and final evaluation. The participants included 18 eighth-grade students from Class 8A at SMP Negeri 2 Koba in Kepulauan Bangka Belitung Province, along with mathematics teachers from the same school. Data collection instruments included expert evaluation questionnaires for media and material assessment, a student interest questionnaire, and post-test evaluations. Qualitative data were analyzed by summarizing feedback from experts and students, while quantitative data were derived from questionnaire responses and test results. Validation results showed average scores of 4.51 (out of 5) from media experts and 4.93 (out of 5) from material experts, both categorized as